1953
DOI: 10.1210/jcem-13-9-1140
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Precursors of Urinary Dehydroisoandrosterone

Abstract: E VER since dehydroisoandrosterone was first isolated from human urine in 1934 (1) the riddle of its precursor has plagued the biochemist and the clinician. Since it has recently been shown that dehydroisoandrosterone is excreted in normal urine in much larger amounts than hitherto recognized, and therefore that this substance is an important index of normal as well as abnormal adrenal cortical activity, the question of its precursor has assumed added importance. Especially is this true since the estimation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1954
1954
2008
2008

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In the absence of further knowledge, however, it is reasonable to assume that the most active compounds in a closely related series possess groups in a state which actually functions biologically, whereas the less active compounds may first be transformed to the active structures. Lieberman and Teich (22) have made the generalization that, when changes occur during metabolism, steroids are usually transformed chemically to a more highly reduced state.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of further knowledge, however, it is reasonable to assume that the most active compounds in a closely related series possess groups in a state which actually functions biologically, whereas the less active compounds may first be transformed to the active structures. Lieberman and Teich (22) have made the generalization that, when changes occur during metabolism, steroids are usually transformed chemically to a more highly reduced state.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that abnormally large quantities of dehydroisoandrosterone are by no means invariably found in adrenal cortical carcinoma (32). Be-cause the precursor (or precursors) of dehydroisoandrosterone is unknown at this time, the true significance of this steroid as a urinary excretory product is difficult to assess (33,34).…”
mentioning
confidence: 99%
“…One may, however, consider the possibility of a direct action on the adrenal cortex by the oestrogen, particularly as certain steroids have been shown to have a direct stimulatory influence on adrenocortical metabohsm [Brummel, Halkerston & Reiss, 1954]. Lieberman & Teich [1953] have suggested that DHA might arise from 5:3ß: 17-diol C21 metabolites derived from intermediates in the biogenesis of the corticosteroids by hydroxylation at C17 prior to conversion of the A5:3/? : 17-diol group to a A4:3-ketone.…”
Section: Resultsmentioning
confidence: 99%